The vampire diaries - Smith, L. J. (Lisa J.); Smith, L. J. (Lisa J.). (New York : HarperTeen, 2007)
Presents the last two volumes in the Vampire Diaries series in which the struggle of vampire brothers Stefan and Damon over the now-changed Elena comes to its final conclusion.
The fury -- Dark reunion.
Contains two volumes originally published separately.
Keywords: Vampires -- Fiction; Brothers -- Fiction; Supernatural -- Fiction